Предмет: Алгебра,
автор: virtes775
производная 10 класс.
Приложения:
Ответы
Автор ответа:
0
Y=x^3-2x^2+x+2 y'=3x^2=4x+1
y=x^(-2) y'=-2x^(-3)
y=sqrt(x)(2sinx+1) y'=(2sinx+1)/(2sqrt(x))+sqrt(x)(2cosx)
y=tgx+1/x y'=1/cos^2x-1/x^2
y=1/cosx y'=-tgx/cosx y=(3x^2-2)/x^3=3/x-2/x^3 y'=-3/x^2+6x^(-4)
y=x^(-2) y'=-2x^(-3)
y=sqrt(x)(2sinx+1) y'=(2sinx+1)/(2sqrt(x))+sqrt(x)(2cosx)
y=tgx+1/x y'=1/cos^2x-1/x^2
y=1/cosx y'=-tgx/cosx y=(3x^2-2)/x^3=3/x-2/x^3 y'=-3/x^2+6x^(-4)
Похожие вопросы
Предмет: Русский язык,
автор: Bake0000
Предмет: Математика,
автор: ozimova8464
Предмет: Математика,
автор: artemmakeev08
Предмет: Биология,
автор: natyli4kaаа
Предмет: Алгебра,
автор: Extranarik